2016
DOI: 10.1262/jrd.2016-003
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation-mediated transcription factors regulate <i>Piwil1</i> expression during chicken spermatogenesis

Abstract: The P-element induced wimpy testis (Piwi) protein family is responsible for initiating spermatogenesis and maintaining the integrity of germ cells and stem cells, but little is known regarding its transcriptional regulation in poultry. Here, we characterized the methylation status of the Piwil1 promoter in five different spermatogenic cell lines using direct bisulfite pyrosequencing and determined that methylation correlates negatively with germ cell type-specific expression patterns of piwil1. We demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The results of integration networks revealed most of the DEGs and DERs have no interactions in yak testis development and reproduction. Interestingly, AURKA was the only gene in 10 co-expressed genes that have close interactions with HSPA2 , TDRD5 , STAG3 , and PIWIL1 , which are important functional genes for animal reproduction [ 17 , 18 , 31 , 37 ]. In addition, we found that STAG3 is the executive functional gene for proper pairing and segregation of chromosomes during meiosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of integration networks revealed most of the DEGs and DERs have no interactions in yak testis development and reproduction. Interestingly, AURKA was the only gene in 10 co-expressed genes that have close interactions with HSPA2 , TDRD5 , STAG3 , and PIWIL1 , which are important functional genes for animal reproduction [ 17 , 18 , 31 , 37 ]. In addition, we found that STAG3 is the executive functional gene for proper pairing and segregation of chromosomes during meiosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation may affect gene expression without changing the DNA sequence and has been found to be closely related with the formation of some complex phenotypic traits202122 and the occurrence and development of various diseases23. Previous studies have suggested that DNA methylation contributes to chicken domestication24, spermatogenesis25, growth development26, the ageing process27, and disease resistance20. Recently, multiple studies have been conducted to identify the genome-wide methylation profiles of economically important animals21222829.…”
mentioning
confidence: 99%
“…Genome-wide chromatin immunoprecipitation (ChIP) analyses have uncovered thousands of NRF1-binding sites in somatic cells (23,24), indicating much broader roles for NRF1 than have been originally defined. A recent report demonstrated that NRF1 regulates the expression of piwi during chicken spermatogenesis (25). However, as homologous disruption of NRF1 leads to embryonic lethality between 3.5 and 6.5 dpc (26), its physiologic function and target genes in mammalian postnatal spermatogenesis has not been determined.…”
mentioning
confidence: 99%